PENGARUH PENERAPAN MODEL PEMBELAJARAN THINK-PAIR-SHARE BERBANTUAN KARTU TRUTH OR DARE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN DI KELAS IV TAHUN PELAJARAN 2025/2026 - Ariani, Izatun; Husni, Muhammad; Lestarini, Yuniar; Rohini, Rohini (STKIP Persada Khatulistiwa Sintang, 2026)
This study was motivated by the low interest and learning outcomes of fourth-grade students in Civics (PPKn) at SDN 2 Banjarsari, caused by less interactive learning processes. The purpose of this study was to examine the effect of the Think-Pair-Share (TPS) learning model assisted by Truth or Dare cards on students’ learning outcomes. The research employed an experimental method using a one-group pretest–posttest design. The sample consisted of 20 fourth-grade students. The research instrument was a multiple-choice test measuring learning outcomes. Data were analyzed using a paired samples t-test. The results showed an improvement in the mean score from 72.50 (pretest) to 86.00 (posttest). Hypothesis testing indicated a significance value of 0.000 < 0.05, leading to the rejection of H? and acceptance of H?. In conclusion, the TPS learning model assisted by Truth or Dare cards has a positive and significant effect on improving students’ cognitive learning outcomes. It also contributes to the development of social skills, such as cooperation and confidence in expressing opinions in Civics learning.